A LUMP IN THE THROAT. (29th November 2012) - Williams, J; O'Connell, K; Kinsella, J; Crotty, T; Curran, A; McGuigan, C
Abstract : Case History: A 58-year-old man presented with a 5-year history of, progressive dysarthria and dysphagia. Prior to neurological review he was diagnosed with obstructive sleep apnoea syndrome. Examination revealed dysarthria and left hypoglossal and glossopharyngeal nerve palsies. Neck palpation was normal. Blood tests including vasculitic screen, serum ACE and anti-acetylcholinesterase antibodies were normal. A contrast enhanced MRI scan of brain and CSF analysis were unremarkable. EMG of tongue and neck muscles revealed no evidence of anterior horn cell or neuromuscular junction dysfunction. A CT thorax revealed several lung nodules but these lesions had disappeared on repeat imaging. A whole body CT-PET scan identified increased uptake in the neck suggestive of lympadenopathy. The presumed nodes were biopsied and histology revealed carotid body paragangliomas. An MR angiogram performed at a later date showed large vascular neck masses (figure 1). Following diagnosis he also developed bilateral Horner's Syndrome. Discussion: This patient presents with progressive dysarthria, dysphagia and Horner's syndrome secondary to bilateral carotid paragangliomas. Carotid paragangliomas are rare neuroendocrine tumours. They are usually benign, presenting as a painless cervical mass. Up to 25% are hereditary especially when bilateral. Management includes surgical resection if small or radiotherapy to reduce expansion of larger masses. It later transpired our patient had a family history of individuals with neck tumours and the results of genetic testing are awaited.